Effect of non-steroidal anti-inflammatory ophthalmic solution on intraocular pressure reduction by latanoprost in patients with primary open angle glaucoma or ocular hypertension. Issue 3 (17th February 2006) - Chiba, T; Kashiwagi, K; Chiba, N; Tsukahara, S
Abstract : Aim: To investigate the effects of a non-steroidal anti-inflammatory drug (NSAID) ophthalmic solution on latanoprost induced intraocular pressure (IOP) reduction in glaucoma patients. Methods: Examination was conducted on 16 eyes of 16 glaucoma patients who had been given only latanoprost for at least 6 weeks. The NSAID ophthalmic solution, sodium 2-amino-3-(4-bromobenzoyl) phenylacetate sesquihydrate, was additionally given for 12 weeks into one eye (NSAID group), while sodium hyaluronic acid ophthalmic solution was administered into the other eye (control group) in a double masked fashion. The IOP measurement was performed before the start of additional administration of ophthalmic solutions, 2, 4, 6, 8, 10, and 12 weeks after the start of additional administration, and 2, 4, and 6 weeks after discontinuing additional administration. Results: No significant difference was observed in the IOPs before additional administration of ophthalmic solution between the NSAID group and the control group. Following the additional administration of ophthalmic solution, IOP in the NSAID group was consistently higher than that in the control group, and a maximum difference in IOP between the two groups was 1.08 (SD 1.75) mm Hg (p = 0.03). This trend was observed even after additional administration was discontinued. Conclusion: NSAID ophthalmic solution may partly affect IOP reduction by latanoprost.